MATHEMATICAL CONNECTION ABILITY AND SELF-CONFIDENCE (An experiment on Junior High School students through Contextual Teaching and learning with Mathematical Manipulative) - Hendriana, Heris; Rahmat Slamet, Ujang; Sumarmo, Utari (UPI Press, 2014)
This sudy was intended to examine the role of prior mathematics ability (PMA) and contextual teaching approach with mathematical manipulative (CTL-MM) to the achievement of mathematical connection ability (MCA) and self-confidence (SC) of junior high school students. This study was part of a master thesis, and it was a sub-study of a Postgraduate Research Grant from DGHE in 2013 as well. The study was quasi-experimental with pre-test post-test control group design, involving 67 ninth-grade students from a junior high school in Bandung. The instruments of this study were an essay test on mathematical connection, a self-confidence scale, and a scale on students’ perception toward CTL-MM. The result of the study revealed that CTL-MM was better in improving students’ MCA, N-Gain of MCA, and SC. This was shown by students’ grades of MCA and SC which were better in the group taught by CTL-MM than students’ grades in the group taught by conventional teaching. While their grades of SC were better, the grades of MCTA were at low level. However, there was a moderate correlation between mathematical connection and self-confidence though students demonstrated positive perception toward the implementation of CTL-MM.